If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1A + -5B + 2) * 5AB = 0 Reorder the terms: (2 + -1A + -5B) * 5AB = 0 Reorder the terms for easier multiplication: 5AB(2 + -1A + -5B) = 0 (2 * 5AB + -1A * 5AB + -5B * 5AB) = 0 Reorder the terms: (10AB + -25AB2 + -5A2B) = 0 (10AB + -25AB2 + -5A2B) = 0 Solving 10AB + -25AB2 + -5A2B = 0 Solving for variable 'A'. Factor out the Greatest Common Factor (GCF), '5AB'. 5AB(2 + -5B + -1A) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'AB' equal to zero and attempt to solve: Simplifying AB = 0 Solving AB = 0 Move all terms containing A to the left, all other terms to the right. Simplifying AB = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(2 + -5B + -1A)' equal to zero and attempt to solve: Simplifying 2 + -5B + -1A = 0 Reorder the terms: 2 + -1A + -5B = 0 Solving 2 + -1A + -5B = 0 Move all terms containing A to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -1A + -2 + -5B = 0 + -2 Reorder the terms: 2 + -2 + -1A + -5B = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1A + -5B = 0 + -2 -1A + -5B = 0 + -2 Combine like terms: 0 + -2 = -2 -1A + -5B = -2 Add '5B' to each side of the equation. -1A + -5B + 5B = -2 + 5B Combine like terms: -5B + 5B = 0 -1A + 0 = -2 + 5B -1A = -2 + 5B Divide each side by '-1'. A = 2 + -5B Simplifying A = 2 + -5BSolution
A = {2 + -5B}
| -4+6x=-34 | | 0.3(r+2)=-1.0(-2r-4) | | 6t^2+2t=2t(3t+1) | | 2y+3=3(0)-7 | | -7(p-8)= | | -2v-14=8(v+2) | | 4t=38+2t | | n-8=22+4 | | 3(4+4n)=18n+12-6n | | -5(x+7)= | | (2x+4)x=240 | | 6/15=3/x | | 2n^2=90 | | x(6)=60 | | n+3=17+4 | | 9h+11=5h-17 | | 2x(2x)= | | x(13)=52 | | 8x+9y=818 | | 400-313=x | | 6(b+4)=0 | | -9(6+u)=2u-10 | | 132=12(n+9) | | -8x+4(1+5x)=-6-14 | | 1/3x+2=1/2x+3 | | 2x^2+22x+121= | | 25x=1.2 | | 4x+7y=54 | | 3+9q=4+8q | | 16-r=16 | | 35r+500= | | 5x-17=133 |